The city and region in the current urbanism: two articulated systems (2019)
The work explores the relationships that emerge between the city and theregion within the new dynamics that has taken the urbanization in the world,starting to understand both systems as geo-socio-historical products that arearticulated in its development, a process that has as one of its most notablespatial manifestations the city-region